Neoliberal governance and 'responsibilization' of agents: reassessing the mechanisms of responsibility-shift in neoliberal discursive environments. Issue 2 (4th May 2017) - Pyysiäinen, Jarkko; Halpin, Darren; Guilfoyle, Andrew
ABSTRACT: The 'governmentality' approach has been influential in analyzing how neoliberal governance transfers responsibility to individual agents through an 'appeal of freedom' mechanism. This productive conceptualization of power has generated a solid body of research on the workings of (neo)liberal governance and contemporary Western capitalism. However, such research has largely ignored a complementary mechanism characteristic of situations where 'appeal of freedom' lets actors down, that is, dynamics of 'threat to personal control'. Studies focusing and elaborating on this aspect, and 'control constructs' more generally, have remained mostly within the disciplinary boundaries of (social) psychology. In this paper we aim to bring the social psychological research on control constructs into a dialogue with governmentality theorizing and to show how neoliberal 'responsibilization' can work through threats to personal control, insecurity and governance by fear. We propose one way of utilizing, and advancing, these approaches in tandem with empirical research, by focusing on the analysis of control attributions of the subjects of (neoliberal) governance. With a brief empirical illustration from the context of Australian neoliberal agricultural policies we then show how neoliberal 'responsibilization' can be viewed as relying on farmers' striving to maintain personal control under uncertainty, in addition to the workings of the 'appeal of freedom' mechanism.